Cardiac Auscultation for Noncardiologists: Application in Cardiac Rehabilitation Programs. Issue 6 (November 2017) - Compostella, Leonida; Russo, Nicola; Compostella, Caterina; Setzu, Tiziana; Iliceto, Sabino; Bellotto, Fabio
Abstract : This clinical skills review describes the most common cardiac auscultatory findings in adults after heart surgery and correlates them with prognostic indicators. It was written for noncardiologist health care providers who work in outpatient cardiac rehabilitation programs. Mechanical prosthetic valves produce typical closing and opening clicks. Listening to their timing and features, as well as to presence and quality of murmurs, contributes to the awareness of potential prosthesis malfunction before other dramatic clinical signs or symptoms become evident. In patients with biological prostheses, murmurs should be carefully evaluated to rule out both valve malfunction and degeneration. Rubs of post-pericardiotomy pericarditis should prompt further investigation for early signs of cardiac tamponade. Third and fourth heart sounds and systolic murmurs in anemic patients should be differentiated from pathological conditions. Relatively new groups of heart surgery patients are those with chronic heart failure treated with continuous-flow left ventricle assist devices. These devices produce characteristic continuous noise that may suddenly disappear or vary in quality and intensity with device malfunction. After heart transplantation, a carefully performed and regularly repeated cardiac auscultation may contribute to suspicion of impending acute rejection. During cardiac rehabilitation, periodic cardiac auscultation may provide useful information regarding clinical-hemodynamic status and allow detection of heralding signs of possible complications in an efficient and low-cost manner. Abstract : The most significant common cardiac auscultatory findings present in adult patients during cardiac rehabilitation after various types of heart surgery are presented and related to some prognostic indicators. Periodic cardiac auscultation is an efficient and low-cost tool for assessment of patients during early cardiac rehabilitation.